Rediscovery and new morphological data on two Hassalstrongylus (Nematoda: Heligmonellidae) coparasitic in the marsh rat Holochilus chacarius (Rodentia: Cricetidae) from Argentina - Notarnicola, Juliana (2015)
Two species of Hassalstrongylus Durette-Desset, 1971, coparasitic in Holochilus chacarius Thomas (Rodentia, Cricetidae) and not recorded since their original description in 1937, were newly found in their type host and locality. Hassalstrongylus mazzai (Freitas, Lent and Almeida, 1937) and Hassalstrongylus argentinus (Freitas, Lent and Almeida, 1937) were obtained from Ho. chacarius from 2 different populations: one from Salta Province (northwest Argentina) and another from Chaco Province (northeast Argentina). The species described as Heligmonoides mazzai Freitas, Lent and Almeida, 1937 had been transferred to Hassalstrongylus even though its synlophe had never been studied. We provide the first descriptions and illustrations of the synlophe of males and females of Hassalstrongylus mazzai and the female of H. argentinus and account for morphological and metrical variability. We confirm, through the study of the synlophe, the placement of Hassalstrongylus mazzai in the genus Hassalstrongylus and designate neotypes for the species because the type material deposited by the authors could not be found. Females of both species were morphologically very similar, and a principal components analysis (PCA) performed on some morphometrical characters showed that the body length, uterus length, and an unexpected character as the number of eggs were useful characters in the discrimination of both species.